Mutual coupling reduction in Fabry‐Pérot cavity antenna array. Issue 7 (21st March 2020) - Zhan, Junlin; Xu, Feng; Liu, Shui; Deng, Senshen; Yang, Ling; Qiang, Jingxia
Abstract: This letter presents the mutual coupling reduction in Fabry‐Pérot (FP) cavity antenna array. Partially reflecting surface (PRS) and analogous artificial magnetic conductor reflectarray in the cavity participate in phase and magnitude modulation with spatial decoupling solution. With the proper design for the cells of PRS and reflectarray, along with the distance between them, scattered and surface waves are analyzed independently to achieve the trade‐off between mutual coupling reduction and high directivity. With decoupling optimization, S 21 decreases from −20 to −30 dB, and the gain of the decoupling FP cavity antenna array fed by single source drops acceptably from 14.3 to 13.6 dBi simultaneously. The low E ‐plane coupling coefficient and envelope correlation coefficient are achieved. Besides, the height of the decoupling FP cavity antenna array is lower than 6.3 mm owing to the participation of reflectarray. That the measured results are in good agreements with simulated results verifies the decoupling FP cavity antenna array performances.